Sesquiterpene lactones. XXXIV. Guaianolides in the genus Leuzea DC. - Gerard Nowak; Miroslav Holub; Miloš Buděšínský (Acta Societatis Botanicorum Poloniae, 2014)
Guaianolides were found in three species of the genus Leuzea DC. Chlorojanerin, cynaropicrin and janerin were isolated from L. rhapontica subg. helenifolia (Gren, Gordon) Holub and L. rhaponticoides Graells. From L. carthamoides (Willd.) DC., chlorojanerin, cynaropicrin, janerin, cebellin E and repdiolide were obtained.